2016
DOI: 10.1002/hed.24542
|View full text |Cite
|
Sign up to set email alerts
|

Increasing use of nonsurgical therapy in advanced‐stage oral cavity cancer: A population‐based study

Abstract: Utilization of nonsurgical therapy for advanced-stage oral cavity SCC is increasing and is independently associated with a reduction in survival, as well as patient factors traditionally associated with reduced access to medical care and advanced T and N classifications. © 2016 Wiley Periodicals, Inc. Head Neck 39: 82-91, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 49 publications
1
19
0
2
Order By: Relevance
“…Much of our cohort underwent primary surgery (43.8%) and exhibited a remarkably higher 5‐year DSS (80%) compared with those undergoing RT alone (27%) and those treated with combined surgery and RT (53%). This finding is reinforced by Cannon et al, who identified superior 5‐year DSS of oral cavity cancers treated with surgery alone compared with nonsurgical approaches . Furthermore, our data revealed that surgery was an independent predictor of improved OS and DSS (Table ).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Much of our cohort underwent primary surgery (43.8%) and exhibited a remarkably higher 5‐year DSS (80%) compared with those undergoing RT alone (27%) and those treated with combined surgery and RT (53%). This finding is reinforced by Cannon et al, who identified superior 5‐year DSS of oral cavity cancers treated with surgery alone compared with nonsurgical approaches . Furthermore, our data revealed that surgery was an independent predictor of improved OS and DSS (Table ).…”
Section: Discussionsupporting
confidence: 82%
“…Importantly, definitive RT was an independent predictor of worse OS (HR 1.6; P < 0.001) (Table ) and DSS (HR 2.29; P < 0.001) (Table ). This trend is further supported by Cannon et al, who showed inferior survival outcomes in patients with oral cavity cancer who were treated with nonsurgical approaches …”
Section: Discussionmentioning
confidence: 60%
“…Interestingly, the use of nonsurgical treatment for early‐stage disease is significantly less than has been recently reported for advanced‐stage oral cancer . Additionally, in contrast to advanced‐stage disease, the use of radiation in early‐stage disease is decreasing.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, the use of nonsurgical treatment for earlystage disease is significantly less than has been recently reported for advanced-stage oral cancer. 23 Additionally, in contrast to advanced-stage disease, the use of radiation in early-stage disease is decreasing. This suggests a widening disconnect between how treatment choices are made for early-stage and advanced-stage oral cancer, perhaps because of the publication of multiple trials evaluating the use of concurrent chemoradiation in advanced-stage unresectable head and neck cancers during the study's time period.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative radiation therapy is commonly recommended in several clinical scenarios for head and neck squamous cell carcinoma, and is known to improve survival for positive surgical margins. [28][29][30][31] The goal of this study is to analyze data from the NCDB to investigate whether treatment with adjuvant radiation improves overall survival in adult head and neck sarcoma patients with positive surgical margins as well as compare trends in utilization using an aggregated national dataset.…”
Section: Introductionmentioning
confidence: 99%